Development and performance assessment power generating systems using clean hydrogen - Oruc, Onur; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
In this study, three possible reactions of aluminum - water are considered for clean hydrogen production. The utilization of this clean hydrogen through the two concepts of power generation is investigated thermodynamically. The evaluated first power generation facility based on Al - water reaction has an open cycle gas turbine, steam turbine, boiler, reactor and grinder. The second power generation facility has a fuel cell, a reactor and a grinder. The hydrogen generation resulting from the reactions then the conversion of this hydrogen into energy using turbines or fuel cell and the total exergy destruction are examined comparatively. A thermodynamic analysis is performed with the help of EES (Engineering Equation Solver) software based on the equilibrium reactions in steady state regime. The amount of water required for the hydrogen production is investigated and it is found that the energy efficiencies for the three methods are directly proportional to the amount of water. The energy efficiency for the method 1 based on Bayerite reaction is 38%, the energy efficiency for the method 2 based on boehmite reaction is 56% and the method 3 based on aluminum oxide reaction is 73%. The exergy efficiencies for all methods are calculated at around 41%. When two different power generation concepts are examined, it is observed that combustion-based energy production is more efficient in terms of both energy efficiency and exergy efficiencies. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Energy; Exergy; Efficiency; Aluminum-water reactions; Hydrogen production; Power generation; ALUMINUM; HYDROLYSIS; COMBUSTION; FUELS; Thermodynamics; Energy & Fuels